LY2109761 attenuates radiation-induced pulmonary murine fibrosis via reversal of TGF-β and BMP-associated proinflammatory and proangiogenic signals - Flechsig, Paul; Bickelhaupt, Sebastian; Jenne, Jürgen; Timke, Carmen; Peschke, Peter; Huber, Peter E. (Clinical cancer research, 2012)
Purpose: Radiotherapy is used for the treatment of lung cancer, but at the same time induces acute pneumonitis and subsequent pulmonary fibrosis, where TGF-β signaling is considered to play an important role. Experimental Design: We irradiated thoraces of C57BL/6 mice (single dose, 20 Gy) and administered them a novel small-molecule TGF-β receptor I serine/threonine kinase inhibitor (LY2109761) orally for 4 weeks before, during, or after radiation. Noninvasive lung imaging including volume computed tomography (VCT) and MRI was conducted 6, 16, and 20 weeks after irradiation and was correlated to histologic findings. Expression profiling analysis and protein analysis was conducted in human primary fibroblasts. Results: Radiation alone induced acute pulmonary inflammation and lung fibrosis after 16 weeks associated with reduced life span. VCT, MRI, and histology showed that LY2109761 markedly reduced inflammation and pulmonary fibrosis resulting in prolonged survival. Mechanistically, we found that LY2109761 reduced p-SMAD2 and p-SMAD1 expression, and transcriptomics revealed that LY2109761 suppressed expression of genes involved in canonical and noncanonical TGF-β signaling and downstream signaling of bone morphogenetic proteins (BMP). LY2109761 also suppressed radiation-induced inflammatory [e.g., interleukin (IL)-6, IL-7R, IL-8] and proangiogenic genes (e.g., ID1) indicating that LY2109761 achieves its antifibrotic effect by suppressing radiation-induced proinflammatory, proangiogenic, and profibrotic signals. Conclusion: Small-molecule inhibitors of the TGF-β receptor I kinase may offer a promising approach to treat or attenuate radiation-induced lung toxicity or other diseases associated with fibrosis. Clin Cancer Res; 18(13); 3616-27. ©2012 AACR.
Published online first April 30, 2012
Gesehen am 06.08.2019